2009
DOI: 10.1073/pnas.0908082106
|View full text |Cite
|
Sign up to set email alerts
|

NMR reveals pathway for ferric mineral precursors to the central cavity of ferritin

Abstract: Ferritin is a multimeric nanocage protein that directs the reversible biomineralization of iron. At the catalytic ferroxidase site two iron (II) ions react with dioxygen to form diferric species. In order to study the pathway of iron(III) from the ferroxidase site to the central cavity a new NMR strategy was developed to manage the investigation of a system composed of 24 monomers of 20 kDa each. The strategy is based on 13 C-13 C solution NOESY experiments combined with solid-state proton-driven 13 C-13 C spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
202
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(215 citation statements)
references
References 38 publications
8
202
1
2
Order By: Relevance
“…1) suggest roles beyond just electrostatics for the conserved carboxylates, such as ion selectivity at the channel constriction or directing Fe 2ϩ substrate ions to active sites in three subunits that also form the entry channels (10). The Fe 3ϩ O nucleation channels were recently identified using 13 (10) and earlier studies (16,17), and on residues in the Fe 3ϩ postoxidation/nucleation channel, identified by NMR spectroscopy (11). Our results show that conserved carboxylates in the Fe 2ϩ ion entry channels, connecting the external cage surface to the central, mineralization cavity (Fig.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…1) suggest roles beyond just electrostatics for the conserved carboxylates, such as ion selectivity at the channel constriction or directing Fe 2ϩ substrate ions to active sites in three subunits that also form the entry channels (10). The Fe 3ϩ O nucleation channels were recently identified using 13 (10) and earlier studies (16,17), and on residues in the Fe 3ϩ postoxidation/nucleation channel, identified by NMR spectroscopy (11). Our results show that conserved carboxylates in the Fe 2ϩ ion entry channels, connecting the external cage surface to the central, mineralization cavity (Fig.…”
supporting
confidence: 58%
“…1C). The role of the protein in mineral buildup, beyond the catalytic reactions at the catalytic (oxidoreductase or ferroxidase) centers, has only recently been suggested by structural studies (11), which show that nucleation occurs inside the long (ϳ20 Å) Fe 3ϩ O nucleation channels (Fig. 1, A-C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, the biomineralization reaction in H-ferritin cages does not require a nucleation site (24,25), and His57 and Glu61 are involved in controlling the access of ferrous ions to the ferroxidase site (6); the reaction at the ferroxidase site is much faster than in L-subunits, with time scales for the iron oxidation in homopolymeric H-cages of <1 s. Even with a low number of H-subunits (1 to 2 per cage), the reaction rate is dominated by the catalytic oxidation of iron occurring at the ferroxidase sites. The formation of ferric clusters of high nuclearity in ferroxidase-active (H or H′) subunits has been inferred from Mössbauer data (26)(27)(28) and NMR data (29,30), but these clusters have never been detected by time-lapse anomalous crystallography approaches. This observation supports the occurrence of a different iron mineralization process in ferroxidase-active subunits, leading to spatially disordered clusters that escape detection by X-ray crystallography.…”
Section: Discussionmentioning
confidence: 99%
“…For the solid‐state NMR investigation, ANSII (either free or its MenC conjugate) was freeze‐dried, packed into the magic‐angle spinning (MAS) rotors, then rehydrated to restore the resolution 30, 34, 35, 36. The spectra collected on the pelleted ANSII‐MenC conjugate (Figure 2) are largely superimposable to those of the native and PEGylated forms of the enzyme (see Figure S2 in the Supporting Information) making possible the assessment of the preservation of the protein fold after conjugation with the MenC polysaccharide 37, 38, 39, 40. The resonances of the protein residues were easily reassigned starting from the assignment of the native form of ANSII, by using a carbon‐detection approach (Figure S3) 41.…”
mentioning
confidence: 99%